Analysis of the Protective Immunity Induced by Herpes Simplex Virus 1 Strain M3 with an Attenuated Phenotype Due to Mutations in the Viral ul7, ul41, and LAT Genes - Xu, Xingli; Fan, Shengtao; Wang, Xi; Hu, Yunguang; Feng, Min; Wang, Lichun; Zhang, Ying; Liao, Yun; Zhang, Xiaolong; Li, Qihan (Frontiers in Microbiology, 2017)
Herpes simplex virus 1 (HSV1) is an important pathogen with a worldwide epidemic trend that affects populations of various ages. It has a high morbidity, particularly in juveniles, but a successful HSV1 vaccine is not currently available. Thus, our study systematically observed the immune responses induced in mice immunized with the attenuated HSV1 M3 mutant strain, which has mutations in the genes encoding the UL7 and Vhs tegument proteins and the latency associated transcript (LAT). The immunity induced by the M3 mutant strain can control acute viral infection during HSV1 wild-type strain infection. Moreover, this immunity exerts a potent effect on controling the virus entering the trigeminal neurons. These data encourage further studies investigating the development of M3 as a potential vaccine candidate, and much work is necessary to evaluate the efficiency and safety of this strain.